The development and validation of a radiological Decision Aid to determine suitability for medial unicompartmental knee replacement - Hamilton, T; Pandit, H; Lombardi, A; Adams, J; Oosthuizen, C; Clave, A; Dodd, C; Berend, K; Murray, D (British Editorial Society of Bone and Joint Surgery, 2016)
Aims An evidence based radiographic Decision Aid for meniscal-bearing unicompartmental knee replacement (UKR) has been developed and this study investigates its performance at an independent centre. Patients and Methods Pre-operative radiographs, including stress views, from a consecutive cohort of 550 knees undergoing replacement (UKR or TKR) by a single-surgeon were assessed. Suitability for UKR was determined using the Decision Aid with the assessor blinded to treatment received. Results The sensitivity and specificity of the Decision Aid was 92% and 88% respectively. Excluding knees where a clear pre-operative plan was made to perform TKR, i.e. patient request, the sensitivity was 93% and specificity 96%. The false-positive rate was low (2.3%) with all readily identifiable during joint inspection at surgery. In patients meeting Decision Aid criteria and receiving UKR the 5-year survival was 99% (95%CI 97 to 100%). The false-negatives (3.3%), who received UKR, but did not meet criteria, had significantly worse functional outcomes (flexion (p<0.001), AKSS-Functional (p<0.001), UCLA (p=0.04)), and lower implant survival 93.1% (95%CI 77.6 – 100%). Conclusion The radiographic Decision Aid safely and reliably identifies appropriate patients for meniscal-bearing UKR and achieves good results in this population. The widespread use of the Decision Aid should improve the results of UKR.